Adaptive fuzzy based optimized proportional‐integral controller to mitigate the frequency oscillation of multi‐area photovoltaic thermal system. (27th September 2020) - Gulzar, Muhammad M.; Sibtain, Daud; Murtaza, Ali F.; Murawwat, Sadia; Saadi, Muhammad; Jameel, Ahlam
Abstract: Background: The unprecedented growth in human population and industrialization, the present‐day energy demands have soared dramatically. Therefore, it is essential to integrate renewable energy resources with the conventional ones to keep the energy demand and supply at equilibrium. Aims: While integrating these two energy resources, it is important that the power generated through renewable energy resources should be able to sustain inherent variability and uncertainty of conventional resources. The interaction of renewable into thermal power system degrades the frequency and it is important to mitigate such a problem by introducing an optimal controller. Materials & Methods: In this paper, an optimized Adaptive Fuzzy Logic Controller based Proportional‐Integral (AFLC‐PI) is proposed for Load Frequency Control (LFC) for a multi‐area system. The proposed controller has the capability to tune the Proportional‐Integral (PI) controller on the basis of frequency error, frequency oscillations and minimize the LFC problem for Photovoltaic (PV) connected thermal system. Moreover, the Adaptive Fuzzy Logic Controller (AFLC) response under different real‐time load changing conditions is simulated and analyzed along with the uncertainty in governor and turbine time‐constant. Finally, the comparison analysis with Fuzzy Logic Controller tuned PI (FLC‐PI), Genetic Algorithm tuned PI (GA‐PI) and Firefly tuned PI (FA‐PI) based optimized controllers is carried out. Results: We have analyzed our proposed controller response at various load variations, under critical load variation and observed how fast our proposed technique mitigates the frequency oscillations. Discussion: The results clearly depict that the proposed controller is meeting the critical targets (undershoot, overshoot and settling time) under varying load conditions, sudden variation in a turbine, and governor where AFLC‐PI has the ability to deal any ambiguity in a system effectively. Conclusion: The proposed controller mitigate the frequency oscillation in a robust way as compared to other state of the art controllers. Abstract : This paper presents three area PV connected thermal system, where the influence of PV under 45% penetration is analyzed and keeping the real‐time load variation influence in contact. To cater the challenge adaptive fuzzy logic tuned PI controller is proposed to suppress the frequency oscillation under load perturbation. The proposed controller is designed is such a way that it deals with two factor: LFC requirement and attenuation factor and handle any uncertainty in the system in an abrupt way.